Factors Associated with Infant Mortality due to Congenital Anomalies: A Population-Based Case-Control Study - Fatemeh Zolfizadeh; Maryam ghorbani; Maryam Soltani; Shahab Rezaeian; Abdolhalim Rajabi; Koorosh Etemad; Mahmoud Hajipour; Ali Ghasemi; Halimeh Yaghoobi (Tehran University of Medical Sciences, 2022)
Background: Congenital anomalies are one of the major public health problems and one of the leading cause of infant mortality and morbidity. We aimed to investigate some factors associated with infant mortality due to congenital anomalies in several provinces of Iran. Methods: This case-control study was conducted on 2199 women referring health centers of nine provinces of Iran 2015-2018. Cases were defined as mothers with infant death due to congenital anomalies, and control group comprised of mothers with live birth or infant deaths due to other causes (n=1986). The descriptive data were expressed as percentage and frequency. Factors associated with infant death due to congenital anomalies were evaluated and analyzed at 95% confidence level by logistic regression analysis. Results: The multiple logistic regression analysis reveal that history of cesarean delivery [OR:2.13 ;95%CI (1.58-2.87)], maternal age [OR:1.94 ;95%CI (1.31-2.86)])], area of living [OR: 1.69;95%CI (1.22-2.33)], maternal smoking during pregnancy [OR: 1.41; 95%CI (1.02-1.95)], consanguineous marriage [OR:1.53;95%CI (1.12-2.08)], also low birth weight [OR: 3.09; 95%CI (2.23-4.30)] were significantly associated with infant death due to congenital anomalies. Conclusion: Identification of factors associated with congenital anomalies has been shown to reduce treatment costs and medical complications of neonates. Therefore, genetic counseling and educational programs for high-risk women, and prenatal screening are essential to identify and prevent factors contributing to congenital abnormalities.